2018
DOI: 10.3389/fpsyg.2018.02264
|View full text |Cite
|
Sign up to set email alerts
|

Does Exposure to Counterstereotypical Role Models Influence Girls’ and Women’s Gender Stereotypes and Career Choices? A Review of Social Psychological Research

Abstract: Gender roles are formed in early childhood and continue to influence behavior through adolescence and adulthood, including the choice of academic majors and careers. In many countries, men are underrepresented in communal roles in health care, elementary education, and domestic functions (HEED fields, Croft et al., 2015), whereas women are underrepresented in the science, technology, engineering, and mathematical (STEM) fields (Beede et al., 2011) and top leadership positions (Leopold et al., 2016). Theories f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 132 publications
(208 reference statements)
6
115
0
4
Order By: Relevance
“…Research has shown that women and men form gender roles in childhood, largely based on their exposure to media and popular culture (Olsson and Martiny 2018;Steinke, 2017). Media images often depict men and women in traditional gender roles, which can negatively impact the STEM career choices women make (Olsson and Martiny 2018;Bian, Leslie, & Cimpian, 2017). Dou, Hazari, Dabney, Sonnert, and Sadler (2019) found that talking with friends and family about science and consuming science media in childhood were predictive of STEM identity in college.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that women and men form gender roles in childhood, largely based on their exposure to media and popular culture (Olsson and Martiny 2018;Steinke, 2017). Media images often depict men and women in traditional gender roles, which can negatively impact the STEM career choices women make (Olsson and Martiny 2018;Bian, Leslie, & Cimpian, 2017). Dou, Hazari, Dabney, Sonnert, and Sadler (2019) found that talking with friends and family about science and consuming science media in childhood were predictive of STEM identity in college.…”
Section: Introductionmentioning
confidence: 99%
“…23% working in the IT sector in Norway are women, according to Statistics Norway. A similar situation is found across most of the western world (Buse, 2018), while some countries in other parts of the world, like India, have managed to turn the trend by recruiting more women (Raghuram et al, 2018). In Norway there is, however, also a persistent gender division in higher education, with less than 25% women in computing and less than 10% in some IT programmes (SO, 2018).…”
Section: Introduction -Women In It Careers In Norwaymentioning
confidence: 74%
“…Research gives incongruent answers to this. Some studies find that female role models have positive effects, while others show less clear, or even negative effects, in countering gender stereotypes for women in male dominated fields (Drury et al, 2011;Markussen & Røed, 2017;Olsson & Martiny, 2018). Women in male dominated fields might appear as "successful" role models, however, they might also appear to have crossed a boundary and become "absorbed by the masculine culture" (Corneliussen, 2011, p. 97).…”
Section: Literature Review -Role Models In the Male Dominated Field Omentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that childhood gender socialization influences career attainment (Lawson, Crouter, & McHale, 2015). One potential way to challenge the gender socialization that reduces women's self‐efficacy is to expose clients to role models and experiences that challenge socialization (Olsson & Martiny, 2018). Counselors should focus on providing young women, and especially women of color, early exposure to nontraditional careers and build young women's self‐efficacy in a variety of career paths (Olsson & Martiny, 2018).…”
Section: Implications For Contemporary Practice and Future Researchmentioning
confidence: 99%